2011
DOI: 10.4028/www.scientific.net/amr.291-294.964
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Spot Welding between Titanium and Stainless Steel with an Aluminum Alloy Insert

Abstract: The resistance spot welding between commercially pure titanium and stainless steel was achieved using an aluminum alloy insert. The interfacial microstructure and mechanical properties of the joint were investigated. The maximum tensile shear load of 5.38 kN was obtained from the Ti/SUS304 joint welded at the welding current of 10 KA. The results reveal that the property of the Ti/SUS304 joint can be improved by using an aluminum alloy insert between Ti and SUS304 sheet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Resistance spot welding is the most widely used method in the joining of thin metal sheets due to its high effeciency and high degree of automation, in which a small weld is formed between two metal workpieces through localized melting due to interfacial resistance heating. The present study revealed that the spot resistance welding of titanium alloys to themselves and to other materials was successfully performed [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. Especially, the interfacial microstructure mainly consisted of TiAl 3 intermetallics when the the titanium alloys were spot resistance welded to aluminium alloys [ 116 , 120 ], which indicated the possibility of spot resistance welding of titanium aluminides.…”
Section: Joining Of Titanium Aluminides By Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance spot welding is the most widely used method in the joining of thin metal sheets due to its high effeciency and high degree of automation, in which a small weld is formed between two metal workpieces through localized melting due to interfacial resistance heating. The present study revealed that the spot resistance welding of titanium alloys to themselves and to other materials was successfully performed [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. Especially, the interfacial microstructure mainly consisted of TiAl 3 intermetallics when the the titanium alloys were spot resistance welded to aluminium alloys [ 116 , 120 ], which indicated the possibility of spot resistance welding of titanium aluminides.…”
Section: Joining Of Titanium Aluminides By Other Methodsmentioning
confidence: 99%
“…The present study revealed that the spot resistance welding of titanium alloys to themselves and to other materials was successfully performed [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. Especially, the interfacial microstructure mainly consisted of TiAl 3 intermetallics when the the titanium alloys were spot resistance welded to aluminium alloys [ 116 , 120 ], which indicated the possibility of spot resistance welding of titanium aluminides. The dissimilar alloy welds have been produced between Ti-6Al-2Sn-4Zr-2Mo-0.1Si (wt%) and Ti-13.5Al-21.5Nb (wt%) titanium aluminide using capacitor discharge resistantce spot welding [ 119 ].…”
Section: Joining Of Titanium Aluminides By Other Methodsmentioning
confidence: 99%
“…Meanwhile, the recommendations to use an interlayer on the SS–Ti joint have been successfully investigated. The application of Nb, Cu, Ni, Ag, and Al have successfully improved the joint quality of the SS–Ti joint [ 15 , 17 , 18 ]. The other method of interlayer application has been investigated by Winnicki et al for an aluminum and steel joint by implementing the aluminum, nickel, and nickel-aluminum coating as an interlayer.…”
Section: Introductionmentioning
confidence: 99%
“…It can easily be automated, is very flexible, and since the weld gun electrodes are clamped, small gaps between the sheets can be levelled. A number of researchers have applied RSW to dissimilar Al-steel joints [91,163,181,191,232,257,267,297], as well as material combinations including Mg-steel [138], glasssteel [78], Cu-Ni plated steel [178], stainless steel-Ti [253], Ti-Al [193], and Al-Mg [90,106]. The benefits of enabling the RSW of Alsteel would be the re-use of existing infrastructure to join both like and dissimilar material combinations and the significant cost avoidance necessary to retool for a new joining process.…”
Section: Resistance Spot Weldingmentioning
confidence: 99%
“…Choi et al [55] introduced an Al-12Si braze at the faying interface during RSW and created a more uniform interface to the steel, though noted fracture along the IMC-Al base material interface resulting in relatively low strengths. Tu et al [253] welded pure Ti to 304 stainless steel using an A5052 sheet inserted between creating a weld nugget in the Al alloy, a diffusion bond with an IMC of 160 nm between the Ti and Al alloy and an IMC consisting of FeAl 3 and Fe 2 Al 5 between the Al and stainless steel, respectively. Fracture occurred either along this IMC layer, within the Al alloy adjacent to the IMC or along the Ti-Al IMC layer with increasing weld currents.…”
Section: Resistance Spot Weldingmentioning
confidence: 99%